The Presence and Roles of Cats, Monkeys, and Donkeys at Deir el-Medina, Egypt: A Comparison of Representational and Textual Evidence - Pierce , Krystal V.L. (Ash-sharq: Bulletin of the Ancient Near East – Archaeological, Historical and Societal Studies, 2024)
This paper studies the three domesticated mammals at Deir el-Medina that appear the most often in the pictorial and written corpora, namely, cats, monkeys, and donkeys. The article is part of a larger study on non-satirical and non-divine attestations of domesticated mammals at Deir el-Medina, encompassing cats, cattle, dogs, donkeys, goats, horses, monkeys, pigs, and sheep. Some of these animals are portrayed visually in tombs and on objects, but are not mentioned in textual sources, while other animals are referenced in many texts, but rarely in pictorial form.